The Impact of Accounting Measurement and Human Resources Disclosure on Financial Statements in Algerian Institutions Case of "Algerian Water Company" Guelma Unit - sellaoui, rafik (Journal of Research in Finance and Accounting, 2024)
Recently, a debate has emerged regarding whether human resource costs should be recognized as assets in balance sheets or treated as expenses in profit and loss accounts. This research seeks to analyze the accounting measurement and disclosure of human resources, as well as their impact on the financial statements of organizations, which serve as the primary source for decision-making. The researchers adopted a descriptive-analytical approach and conducted an empirical study for this purpose. A questionnaire was developed and distributed to a number of accountants at the 'Algérienne des Eaux' (ADE) unit in Guelma. Among the most prominent findings of the study is that investment in human resources can be considered one of the organization's assets, similar to other intangible assets. Furthermore, the research revealed that accounting disclosure of human resource costs has a tangible impact on the financial statements